Research Progress of Titanium-Based High Entropy Alloy: Methods, Properties, and Applications - Ma, Ning; Liu, Shifeng; Liu, Wei; Xie, Lechun; Wei, Daixiu; Wang, Liqiang; Li, Lanjie; Zhao, Beibei; Wang, Yan (Frontiers in Bioengineering and Biotechnology, 2020)
With the continuous progress and development in the biomedicine field, metallic biomedical materials have attracted the considerable attention of researchers, but the related procedures need to be further developed. Since the traditional metal implant materials are not highly compatible with the human body, the modern materials with excellent mechanical properties and proper biocompatibility should be developed urgently in order to solve any adverse reactions caused by the long-term implantations. The advent of the high-entropy alloy (HEA) as an innovative and advanced idea emerged to develop the medical implant materials through the specific HEA designs. The properties of these HEA materials can be predicted and regulated. In this paper, the progression and application of titanium-based HEAs, as well as their preparation and biological evaluation methods, are comprehensively reviewed. Additionally, the prospects for the development and use of these alloys in implant applications are put forward.